A strategy to complete databases with parameters of refined line shapes and its test for CO in He, Ar and Kr. (December 2017) - Ngo, N.H.; Hartmann, J.-M.
Abstract: We propose a strategy to generate parameters of the Hartmann-Tran profile (HTp) by simultaneously using first principle calculations and broadening coefficients deduced from Voigt/Lorentz fits of experimental spectra. We start from reference absorptions simulated, at pressures between 10 and 950 Torr, using the HTp with parameters recently obtained from high quality experiments for the P(1) and P(17) lines of the 3-0 band of CO in He, Ar and Kr. Using requantized Classical Molecular Dynamics Simulations (rCMDS), we calculate spectra under the same conditions. We then correct them using a single parameter deduced from Lorentzian fits of both reference and calculated absorptions at a single pressure. The corrected rCMDS spectra are then simultaneously fitted using the HTp, yielding the parameters of this model and associated spectra. Comparisons between the retrieved and input (reference) HTp parameters show a quite satisfactory agreement. Furthermore, differences between the reference spectra and those computed with the HT model fitted to the corrected-rCMDS predictions are much smaller than those obtained with a Voigt line shape. Their full amplitudes are in most cases smaller than 1%, and often below 0.5%, of the peak absorption. This opens the route to completing spectroscopic databases using calculations and the very numerous broadening coefficients available from Voigt fits of laboratory spectra. Graphical abstract: fx1 Highlights: Direct calculations of individual lineshapes in a broad pressure range. Prediction of some parameters of the Hartmann Tran profile. Considerable improvement with respect to the Voigt profile. Agreement with measured absorptions better than 1%.